Evolução dos níveis de beta-hCG após tratamento sistêmico da gravidez ectópica íntegra - Elito Junior, Julio [UNIFESP] (1998)
OBJECTIVE: The follow-up of this treatment is done by monitorization of beta-hCG titers. The objective of this study is to evaluate the beta-hCG titers after treatment with MTX. METHODS:. Twenty four women were included in the study. The inclusion criteria were: ectopic pregnancy < 4.5cm, beta-hCG < 15.000mIU/mL, desire of future pregnancy and a written permission to participate in the study. All patients were treated with a single dose of methotrexate (50mg/m² IM). Patients were monitored with beta-hCG titers on days 1, 4 and 7 after the MTX injection, and then weekly until the beta-hCG was less than 25mIU/mL. RESULTS: The variation of the titers of beta-hCG between day 1 and day 4 after MTX was the following: increase 50,0%, decrease 33.3% and in levels less than 25mUI/mL in 16.7% of the cases. The variation of the titers of beta-hCG between day 4 and day 7 after MTX was the following: decline > 15% in 85.7% of the cases, and decline < 15% in 14.3%. There was the necessity of a second dose of MTX in only two cases (8.4%), since the levels of beta-hCG declined less than 15%, in this period. CONCLUSION: The titers of beta-hCG increase in 50.0% of the cases, so it is a frequent event. The understanding of this evolution of beta-hCG titers avoids surgery in the first week of the treatment.